Impediments to Nigerian Democracy: The Ambivalent Role of Vigilante Groups in Maintaining Security in the Wake of the Boko Haram Insurgence in Northern Nigeria - Kankara, Ibrahim (Tanzania Journal for Population studies and Development, 2015)
The paper focuses on security efforts of local vigilante groups against the Boko Haram (BH) insurgency in Northern Nigeria. The fight against the BH insurgency is a major source of concern throughout the Nigerian Federation. The use of charms and locally fabricated small arms by the Vigilante and Civilian Joint Task Force (CJTF) is a factor in the fight against BH insurgents. Through data obtained from interviews, newspapers and secondary texts, this article analyses the emergence and role of vigilantes in the fight against insurgency. The groups serve as an alternative security in the areas affected by the insurgency. The groups use a variety of locally made charms in their confrontation with the BH. Furthermore, the paper attempts to evaluate role of the CJTF and Vigilante in the fight against insurgency, and the nature of traditional mechanisms use by the local groups in the fight against the BH insurgency. The paper concludes that there is likelihood for the vigilante to pose a danger to the security in the post-war (against insurgency) period.